How responsive is female labour supply to child care costs: New australian estimates - Xiaodong Gong; Robert Breunig; Anthony King (Institute for the Study of Labor (IZA), 2010)
The degree of responsiveness of Australian women's labour supply to child care cost has been a matter of some debate. There is a view that the level of responsiveness is very low or negligible, running counter to international and anecdotal evidence. In this paper we review the Australian and international literature on labour supply and child care, and provide improved Australian estimates of labour supply elasticities and child care demand elasticities with respect to gross child care price. We find that the limited literature in Australia has suffered from measurement error problems stemming in large part from shortcomings with data on child care price and child care usage. We use detailed child care data from three recent waves of the Household, Income and Labour Dynamics in Australia (HILDA) Survey (covering the period 2005 to 2007) to address these problems. We extend the standard labour supply and child care model to allow for separate effects of different child care prices for children in different age ranges and we calculate regional child care prices based upon child-level information. The salient finding is that child care prices do have statistically significant effects on mothers' labour supply and child care demand. The new estimates are in line with international findings, and their robustness is supported by a validation exercise involving an alternative technique and an earlier time period.
urn:nbn:de:101:1-201010132749
Keywords: J22; J13; 330